Mode-locked thulium–bismuth codoped fiber laser using graphene saturable absorber in ring cavity - Zen, D.I.M.; Saidin, N.; Damanhuri, S.S.A.; Harun, Sulaiman Wadi; Ahmad, Harith; Ismail, M.A.; Dimyati, K.; Halder, A.; Paul, Mukul Chandra; Das, S.; Pal, M.; Bhadra, S.K. (Optical Society of America, 2013)
We demonstrate mode locking of a thulium–bismuth codoped fiber laser (TBFL) operating at 1901.6 nm, using a graphene-based saturable absorber (SA). In this work, a single layer graphene is mechanically exfoliated using the scotch tape method and directly transferred onto the surface of a fiber pigtail to fabricate the SA. The obtained Raman spectrum characteristic indicates that the graphene on the core surface has a single layer. At 1552 nm pump power of 869 mW, the mode-locked TBFL self starts to generate an optical pulse train with a repetition rate of 16.7 MHz and pulse width of 0.37 ps. This is a simple, low-cost, stable, and convenient laser oscillator for applications where eye-safe and low-photon-energy light sources are required, such as sensing and biomedical diagnostics.